How Parkinson's disease meets nucleolar stress - Parlato, Rosanna; Liß, Birgit (Biochimica et biophysica acta, 2014)
Parkinson's disease (PD) is the second most common neurodegenerative disorder. Although the causes of PD are still not understood, aging is a predisposing factor and metabolic stress seems to be a common trigger. Interestingly, the response to stress conditions and quality control mechanisms is impaired in PD, as well as in other neurodegenerative disorders. Downregulation of rRNA transcription is one major strategy to maintain cellular homeostasis under stress conditions, as it limits energy consumption in disadvantageous circumstances. Altered rRNA transcription and disruption of nucleolar integrity are associated with neurodegenerative disorders, and with aging. Nucleolar stress can be triggered by genetic and epigenetic factors, and by specific signaling mechanisms, that are altered in neurodegenerative disorders. The consequences of neuronal nucleolar stress seem to depend on p53 function, the mammalian target of rapamycin (mTOR) activity and deregulation of protein translation. In this review, we will summarize findings identifying an emerging role of nucleolar stress for the onset and progression of in particular PD. Emphasis is given to similarities in molecular causes and consequences of nucleolar stress in other neurodegenerative disorders. The mechanisms by which nucleolar stress participates in PD could help identify novel risk factors, and develop new therapeutic strategies to slow down the progressive loss of neurons in neurodegenerative diseases. This article is part of a Special Issue entitled: Role of the Nucleolus in Human Disease.
Gesehen am 24.08.2020